War, hazards, and economic degradation in Thomond, 1276-1318: agent-based approaches to the Uí Bhriain civil war - Carvalho, Vinicius Marino (2022)
Between 1276 and 1318, English magnates unsuccessfully attempted to establish a lordship in the Irish kingdom of Thomond, Southwestern Ireland, by exploiting a dynastic feud between the then ruling lineage, the Uí Bhriain. The conflict coincided with a series of extreme events that beset Western Europe in the late 13th and early 14th centuries, such as the beginning of the Little Ice Age and the Great European Famine of 1315-1322. The goal of this thesis was to evaluate to which extent the economic degradation at the turn of the 14th century contributed to the failure of the English efforts to politically dominate Thomond. Based on analyses of 13th and 14th centuries written sources, Early Modern cartographical material, and archaeological surveys and excavation reports, I developed an agent-based model (ABM) called ThomondSim, which I used to run experiments measuring political and economic outcomes across different counterfactual scenarii. I also developed a serious board game, The Triumphs of Turlough, which I used to validate ThomondSim\'s historical model and investigate minute and/or non-systematic processes that escaped the \"bird\'s eye\" view provided by the ABM. A quantitative analysis of the experiments\' results interpreted in light of insights from The Triumphs of Turlough\'s playtesting sessions found some correlation between late 13th economic degradation and the fortunes of belligerent factions in the wars of 1276-1318, although it was not expressive enough to have been a crucial factor in the outcome of the conflict.